2009
DOI: 10.1074/jbc.m109.024398
|View full text |Cite
|
Sign up to set email alerts
|

Dynamin2 GTPase and Cortactin Remodel Actin Filaments

Abstract: The large GTPase dynamin, best known for its activities that remodel membranes during endocytosis, also regulates F-actinrich structures, including podosomes, phagocytic cups, actin comet tails, subcortical ruffles, and stress fibers. The mechanisms by which dynamin regulates actin filaments are not known, but an emerging view is that dynamin influences F-actin via its interactions with proteins that interact directly or indirectly with actin filaments. We show here that dynamin2 GTPase activity remodels actin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
115
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(120 citation statements)
references
References 62 publications
4
115
1
Order By: Relevance
“…In contrast, loss-of-function Dyn1K/E-GFP expression did not rescue lamellipodial formation and filopodial number. This further strengthens the idea that Dyn1 is involved in filopodial formation and that, in addition to the known role of GTPase domain in actin remodeling (42), the ABD is also required.…”
Section: Discussionsupporting
confidence: 63%
“…In contrast, loss-of-function Dyn1K/E-GFP expression did not rescue lamellipodial formation and filopodial number. This further strengthens the idea that Dyn1 is involved in filopodial formation and that, in addition to the known role of GTPase domain in actin remodeling (42), the ABD is also required.…”
Section: Discussionsupporting
confidence: 63%
“…For example, interaction between dynamin 2 and cortactin, SH3-domain containing actin binding protein that binds also F-actin and actin-regulating Arp2/3 complex (Ammer & Weed, 2008), is associated with clathrin and dynamin-dependent endocytosis (Krueger et al, 2003;Cao et al, 2003;Zhu et al, 2005). On the other hand, however, the same dynamin-cortactin interaction is considered as a mechanism to recruit dynamin to the site of actin dynamics in other studies Schafer et al, 2002;Mooren et al, 2009;Yamada et al, 2009). Assembly and remodeling of actin filaments by dynamin 2, through an interaction with cortactin, has been investigated by in vitro experiments (Schafer et al, 2002;Mooren et al, 2009).…”
Section: Implication Of Dynamin In Actin Dynamicsmentioning
confidence: 94%
“…On the other hand, however, the same dynamin-cortactin interaction is considered as a mechanism to recruit dynamin to the site of actin dynamics in other studies Schafer et al, 2002;Mooren et al, 2009;Yamada et al, 2009). Assembly and remodeling of actin filaments by dynamin 2, through an interaction with cortactin, has been investigated by in vitro experiments (Schafer et al, 2002;Mooren et al, 2009). In their recent study, they demonstrated that, in the presence of dynamin, GTP led to remodeling of actin filaments in vitro via the actin-binding protein cortactin (Mooren et al, 2009).…”
Section: Implication Of Dynamin In Actin Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations